AUTHENTIC MATERIALS AS A MEDIA FOR TEACHING VOCABULARY - Ika Desy Wardani (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2016)
Problems that happened in English teaching learning activities not only faced by the students, but also by the teacher. For example, most of the students have difficulties in mastering vocabulary. While the teacher has lack of creativities in conducting the teaching instruments, which is challenging for the students, so they do not only depend on the text book and or the worksheets. Authentic text is created to fulfill some social purposes in language community in which the authentic text has been made. The use of authentic text in the written or spoken language could bridge the gap between the students’ problems during the teaching learning activities at the class, and their capacity in practicing their skills in the real life. Key words: authentic material, vocabulary teaching.